Room-temperature unconventional topological Hall effect in a van der Waals ferromagnet Fe3GaTe2 - Hanin Algaidi; Chenhui Zhang; Chen Liu; Yinchang Ma; Dongxing Zheng; Peng Li; Xixiang Zhang (APL Materials)
The prominent properties of van der Waals (vdW) magnets make them a promising platform for prospective spintronic applications. Fe3GaTe2 is a newly discovered vdW material that exhibits room-temperature ferromagnetism and topological spin textures. In this paper, we report the observation of an unconventional topological Hall effect (THE) up to room temperature in Fe3GaTe2. When the current flows along the ab plane, a conventional anomalous Hall effect is observed under an out-of-plane magnetic field, which can be depicted by the intrinsic Karplus–Luttinger mechanism. Intriguingly, by rotating the magnetic field to align with the current direction, unexpected Hall resistivity cusps emerge. This Hall resistivity anomaly can be explained by the in-plane THE, which may originate from the noncoplanar spin structures in Fe3GaTe2. These spin structures have a nonzero scalar spin chirality and act as a fictitious magnetic field that produces a real-space Berry curvature. By extracting the topological Hall resistivity at different temperatures, a THE phase diagram is successfully constructed, showing a maximum value of 1.48 μΩ cm at 250 K. The room-temperature THE reveals the great potential of Fe3GaTe2 for spintronic applications.